Medo odontológico, autopercepção de saúde bucal e fatores associados entre estudantes universitários brasileiros: uma abordagem usando árvore de decisão - Figueiredo, Tayná Ribeiro Monteiro de (2021)
The present study aimed to verify the association between the level of dental fear and the experience of traumatic dental experiences, self-perception of oral health and socio-cultural factors in undergraduate students. It was a cross-sectional observational study, carried out with 633 students from four different courses: Dentistry, Mathematics, Pedagogy and Psychology chosen through simple drawing. Participants answered a self-explanatory questionnaire, containing the Dental Fear Survey - DFS instrument, to assess dental fear. Descriptive statistics were performed and later, all variables were incorporated into the Decision Tree Analysis multivariate model using the CHAID (Chi-squared Automatic Interaction Detector), aiming to identify which are the most relevant factors that influence the level of dental fear. The results of the descriptive statistical analysis showed that the majority of university students were female (71.4%), aged 20 to 24 years (54.0%). 41.5% reported having already had some traumatic experience during dental treatment. The prevalence of a high level of dental fear was 24.5%. Through multivariate analysis using CHAID for the level of dental fear adjusted by the factors investigated among Brazilian university students, it was observed that dental fear could be explained by the report of traumatic dental experiences (p <0.001), course degree that the student was enrolled (p <0.001), self-perceived oral health (p = 0.014) and sex (p = 0.026). The data showed that students who reported traumatic dental experiences, graduates from courses other than dentistry and who rated oral health as poor were more likely to exhibit high levels of dental fear.